2023
DOI: 10.1182/blood.2022018380
|View full text |Cite
|
Sign up to set email alerts
|

The role of CD8+ T cell clones in immune thrombocytopenia

Abstract: Immune thrombocytopenia (ITP) is traditionally considered an antibody-mediated disease. However, a number of features suggest alternative mechanisms of platelet destruction. In this study, we use a multi-dimensional approach to explore the role of cytotoxic CD8+ T cells in ITP. We characterised patients with ITP and compared them to age-matched controls using immunophenotyping, next-generation sequencing of T cell receptor (TCR) genes, single-cell RNA sequencing, and functional T cell and platelet assays. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…In one study of high-dose dexamethasone with rituximab, half the relapsed patients had VbetaTCR clones compared to only one patient in lasting remission. 26 Studies by Stasi et al related response to rituximab to absence of abnormal Tcell populations. 27,28 Addition of an anti-T-cell agent, either MMF as used by one patient, or another agent, might also be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In one study of high-dose dexamethasone with rituximab, half the relapsed patients had VbetaTCR clones compared to only one patient in lasting remission. 26 Studies by Stasi et al related response to rituximab to absence of abnormal Tcell populations. 27,28 Addition of an anti-T-cell agent, either MMF as used by one patient, or another agent, might also be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…11,[50][51][52][53][54][55] In one study, reduction in T-cell receptor diversity was noted in patients followed longitudinally. 56 In addition to potentially serving as a biomarker of more severe disease, clonality may provide insight into the immunoregulatory pathways that contribute to drug resistance. Larger prospective studies are needed to determine whether clonal populations are detectable at initial presentation and/or evolve over time leading to rITP.…”
Section: T-a N D B -Ce L L Dysr Egu L Ation/ Clona L It Ymentioning
confidence: 99%
“…A recent study showed that expanded T‐cell clones are more frequent in patients with rITP (patients with ITP more than 12 months duration and refractory to at least two prior treatment) 8 . Recent evidence suggests that these CD8 T‐cell clones can directly kill platelets by TCR engaging with MHC class I on the platelets, resulting in the release of granzyme and perforin by CD8 T cells, resulting in annexin V and P selectin exposure on platelets, indicating a direct role in killing 9 (Figure 1). The relevant contribution of CD8 T cells to thrombocytopenia needs further understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Activated CD8 T cell TEMRA clones interact with platelets through TCR‐MHC class 1, resulting in the release of perforin and granzyme and the activation and apoptosis of platelets. Source : Blood 2023 9 .…”
Section: Introductionmentioning
confidence: 99%